2020
DOI: 10.3390/molecules26010039
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: A Global Challenge with Old History, Epidemiology and Progress So Far

Abstract: Humans have witnessed three deadly pandemics so far in the twenty-first century which are associated with novel coronaviruses: SARS, Middle East respiratory syndrome (MERS), and COVID-19. All of these viruses, which are responsible for causing acute respiratory tract infections (ARTIs), are highly contagious in nature and/or have caused high mortalities. The recently emerged COVID-19 disease is a highly transmittable viral infection caused by another zoonotic novel coronavirus named severe acute respiratory sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
330
0
64

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(394 citation statements)
references
References 153 publications
0
330
0
64
Order By: Relevance
“…4 The SARS-CoV-2, causes acute respiratory tract infections, is highly contagious in nature causing high mortality. 5 The main symptoms of COVID-19 are fever, dry cough and fatigue, and may be accompanied with nasal congestion, runny nose, sore throat, diarrhea, or loss of taste and smell (anosmia). 6 , 7 Almost all of the patients with COVID-19 have pneumonia, and their chest CT scans show abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…4 The SARS-CoV-2, causes acute respiratory tract infections, is highly contagious in nature causing high mortality. 5 The main symptoms of COVID-19 are fever, dry cough and fatigue, and may be accompanied with nasal congestion, runny nose, sore throat, diarrhea, or loss of taste and smell (anosmia). 6 , 7 Almost all of the patients with COVID-19 have pneumonia, and their chest CT scans show abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that the main concerns related to SARS-CoV-2 are its high transmission potential that has been responsible for the global COVID-19 outbreak [11] , [12] , [13] . The fast-spreading rate of COVID-19 is a result of different transmission methods, including one that is proved to be the most effective: direct contact between humans [14] . This close contact facilitates transmission more rapidly as droplets are expelled through individuals coughing or sneezing [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite India's large population it has a lower infection rate than US, and case fatality rate is the lowest among the top four affected countries. [9] Various factors have been ascribed to the relative resistance of Indians to SARS-Cov-2, including BCG, [10] measles-mumps-rubella vaccines, [11] cross and herd immunity [12] and genomics. [13] It is not known whether the guidelines for management of patients issued by Indian authorities and which were revised from time to time based on available evidence was one of the factors.…”
Section: Introductionmentioning
confidence: 99%